Extraction of supernumerary teeth in a hospital setting: case report in pediatric dentistry - Anne Caroline de Lima PAASHAUS; Vanêssa FAZOLI; Thays Ferreira GISFREDE; Bruno Pereira das POSSES; Kelly Maria Silva MOREIRA; Thais GIMENEZ; José Carlos Pettorossi IMPARATO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT The diagnosis and treatment of supernumerary teeth pose a challenge for dental clinicians and pediatric dentists. These teeth are asymptomatic and may cause the delayed eruption of the permanent dentition, altered bone growth and ectopic positioning. This paper reports a case of the surgical removal of supernumerary teeth in the anterior region of the maxilla of a child under general anesthesia in a hospital setting. A six-year-old female patient visited a private dental office in the city of Garanhuns, Brazil, accompanied by her mother, who reported a tooth with a "strange shape" in the anterior region as the main complaint and also reported that her daughter's first dental experience was negative. The clinical examination and imaging tests were performed under general anesthesia to confirm the diagnosis. In view of the patient's dental and behavioral history, surgical treatment was performed in a hospital setting and assisted by a multidisciplinary team. Care in the hospital setting was found to be feasible, providing greater comfort for uncooperative patients.